PENERAPAN SISTEM INFORMASI INDONESIA PINTAR ENTERPRISE DALAM PENYALURAN BEASISWA PROGRAM INDONESIA PINTAR - Nihan Kristiyani; Azainil; Haeruddin; Muhammad Ramli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of the PIP Program Scholarship is to increase access for school-age children to access services, prevent students from dropping out or not continuing their education due to economic difficulties; and/or attract students who drop out or do not continue in order to return to receive educational services at school. This study aims to determine the implementation of the distribution of PIP Program Scholarships using the SIPINTAR ENTERPRISE Information System Application and to find out the number of recipients at the Public and Private Junior High School Levels in Samarinda City. The method in this study uses a descriptive qualitative method, with observation techniques, information collection in the form of data, literature studies and interviews. As a result of this study, the City of Samarinda through the Education and Culture Office has used the SIPINTAR ENTERPRISE Application and is running well, with the number of recipients as many as 16,620 students out of a total of 33,960 students at the public and private junior high school levels, which is 49.8 percent. Keywords: Information System, PIP, SIPINTAR ENTERPRISE